A Novel Framework for Information Security During the SDLC Implementation Stage: A Systematic Literature Review - Mikael Octavinus Chan; Setiadi Yazid (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2024)
This research delves into the critical aspects of information security during the implementation stage of the Software Development Life Cycle (SDLC). Using a systematic review of the literature, the study synthesizes the findings of various digital repositories, including IEEE Xplore, ACM Digital Library, Scopus, and ScienceDirect, to outline a comprehensive framework that addresses the unique security challenges of the implementation stage. This research contributes to the field by proposing a novel assurance model for software development vendors, focusing on improving information security measures during the implementation stage. The study's findings reveal 12 key steps organizations can adopt to mitigate security risks and improve information security measures during this critical phase. These steps provide actionable insights and strategies designed to support security protocols effectively. The paper concludes that by incorporating these steps, organizations can significantly improve their security posture, ensuring the integrity and reliability of the software development process, particularly during the implementation stage. This approach not only addresses immediate security concerns but also sets a precedent for future research and practice in secure software development, particularly in the critical implementation stage of the SDLC.